FEASTS Combined with Interferometry. IV. Mapping H i Emission to a Limit of NH i = 1017.7 cm−2 in Seven Edge-on Galaxies - Dong Yang; Jing Wang; Zhijie Qu; Zezhong Liang; Xuchen Lin; Simon Weng; Xinkai Chen; Barbara Catinella; Luca Cortese; D. B. Fisher; Luis C. Ho; Yingjie Jing; et al. (The Astrophysical Journal)
We present a statistical study of the neutral atomic hydrogen (H i ) gas extending into the circumgalactic medium perpendicular to the disk for seven edge-on galaxies with inclinations above 85° from the FEASTS program with a 3 σ (20 km s ^−1 ) column density ( N _H _i ) depth of 5 × 10 ^17 cm ^−2 . We develop two photometric methods to separate the extraplanar H i from the disk component based on existing interferometric data and parametric modeling of the disk flux distribution, respectively. With both methods, the FEASTS data exhibit clear extended wings beyond the disk along the minor axis. The extraplanar H i accounts for 5%–20% of the total H i mass and extends to 20–50 kpc at N _H _i = 10 ^18 cm ^−2 . We find a tight positive correlation between vertical extensions of the extraplanar H i and total H i mass M _H _ i . The isodensity shape of H i at N _H _i = 10 ^18 cm ^−2 has an average axis ratio of 0.56 ± 0.11. The off-disk N _H _i profiles of these edge-on galaxies well represent the lower envelope of previous Ly α absorption measurements at low redshift. Our results suggest that at N _H _i = 5 × 10 ^17 cm ^−2 , the H i extends considerably further than the known thin and thick disks in the vertical direction but still remains much flatter than a spherical distribution, consistent with theoretical expectations that outflow, circulation, and accretion should have different impacts in these two directions. We show the tension of our results with Illustris and TNG predictions, highlighting the constraining power of our results for future simulations.